Computer Science and Engineering-Theory and Applications - Sanchez, Mauricio A.; Aguilar, Leocundo; Castañón-Puga, Manuel; Rodríguez-Díaz, Antonio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents a collection of research findings and proposals on computer science and computer engineering, introducing readers to essential concepts, theories, and applications. It also shares perspectives on how cutting-edge and established methodologies and techniques can be used to obtain new and interesting results. Each chapter focuses on a specific aspect of computer science or computer engineering, such as: software engineering, complex systems, computational intelligence, embedded systems, and systems engineering. As such, the book will bring students and professionals alike up to date on key advances in these areas.
A Comprehensive Context-Aware Recommender System Framework -- Executive functions and their relationship with Interaction Design -- Integrating Learning Styles in an Adaptive Hypermedia System with Adaptive Resources -- On Modeling Tacit Knowledge for Intelligent Systems -- Influence of the betweenness centrality to char-acterize the behavior of communication in a group -- Multi-layered Network Modeled with MAS and Network Theory -- A Fuzzy Inference System and Data Mining Toolkit for Agent-Based Simulation in NetLogo -- An Approach to Fuzzy Inference System based Fuzzy Cognitive Maps.
Keywords: Computational intelligence; Dynamics; Nonlinear theories; Artificial intelligence; User interfaces (Computer systems).; Human-computer interaction; Computational Intelligence; Applied Dynamical Systems; Artificial Intelligence; User Interfaces and Human Computer Interaction